Taguchi method approach on effect of lubrication condition on surface roughness in milling operation - Mohamad Syahmi, Shahrom (2012)
This thesis presents an investigation into the MQL (minimum Quantity Lubrication) and wet machining in milling processes of AISI 1060 Aluminum work material with the main objective is to determine the effect of lubrication conditions on the surface roughness. Two types of insert had been used in this research, which is different in geometry selection is radius 0.8mm and 1.2mm. Three other parameters were also considered in this study; feed rate, depth of cut and cutting speed. The levels each parameter had been selected is four levels. The ranges of feed rate 0.05mm/min, 0.15mm/min,0.20mm/min and 0.25mm/min depth of cut used were 0.2mm, 0.4mm, 0.6mm and 0.8mm whereby the cutting speed values were 600mm/min, 800mm/min, 1000mm/min and 1200mm/min. The surface roughness was evaluated using surface roughness tester Mitutoyo. Taguchi method was used to predict the surface roughness. Finally, the experimental results showed good agreement with the estimated results. It was found that, MQL produced better surface finish as compared to wet machining. The result can significantly reduce cost and environmental pollution.